The Relationship of Arm Muscle Strength and Upper Service Skills in The Undana B Men's Volleyball Team - Bani, Ardi Putra Yustisio; Runesi, Salmon; Siahaan, Jurdan Martin; Wijaya, I Nyoman Wahyu Esa; Susanto, Ratno (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Among the general public, volleyball is a tremendously popular sport. From kids to adults, this sport is highly popular with individuals of all ages. Players from the Undana B men's volleyball team used the top serve technique in this study, but it wasn't the best because the ball was frequently caught in the net and, even when it went over the net, would still leave the playing surface. The purpose of this study is to ascertain how Undana B men's volleyball team players' arm muscle strength and upper serve abilities relate to one another. Twelve players from the Undana B men's volleyball team serve as the study samples for this thesis, which employs a quantitative descriptive methodology. Research that seeks to determine the relationship between two variables—specifically, variable X arm muscle strength and variable Y top service skills—is categorized as correlational research. Descriptive statistics, normality, linearity, and correlation tests using the SPSS 22 software are among the analyses needed to meet these standards. The linearity test results indicate a linear connection, and the residual values are normally distributed, according to data analysis from the normality test findings, which indicate that the significant values are 0.818 & 0.634 > 0.05. The high Sig value indicates this. The players' scores indicate a deviation from linearity of 0.221. Given that the analysis's significance level is higher than 0.05, it may be concluded that Ha is accepted and that the Undana B men's volleyball team's service talents and arm muscular strength are significantly correlated. This is evident from the Sig value, which is 0.000 in this study and less than the alpha value, which is 0, 05. The way that variables are interpreted